Answer:
2
Step-by-step explanation:
example A(2a,0),B(2b,0)
C(2b,2c),D(2a,2c)
mid point of AC=((2a+2b)/2,(0+2c)/2)=(a+b,c)
mid point of BD=((2b+2a)/2,(0+2c)/2)=(a+b,c)
∴midpoint of diagonals same or diagonals bisect each other.
Answer:
Step-by-step explanation:
![5^3•5^4 = {5}^{3 + 4} = \purple{ \bold{ {5}^{7} }}](https://tex.z-dn.net/?f=5%5E3%E2%80%A25%5E4%20%3D%20%20%7B5%7D%5E%7B3%20%2B%204%7D%20%20%3D%20%20%5Cpurple%7B%20%5Cbold%7B%20%7B5%7D%5E%7B7%7D%20%7D%7D)
Forty two plus sixty three that's your answer
The value of f[ -4 ] and g°f[-2] are
and 13 respectively.
<h3>What is the value of f[-4] and g°f[-2]?</h3>
Given the function;
![f(x) = \frac{3x-2}{x+1}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B3x-2%7D%7Bx%2B1%7D)
![g(x)=x+5](https://tex.z-dn.net/?f=g%28x%29%3Dx%2B5)
- f[ -4 ] = ?
- g°f[ -2 ] = ?
For f[ -4 ], we substitute -4 for every variable x in the function.
![f(x) = \frac{3x-2}{x+1}\\\\f(-4) = \frac{3(-4)-2}{(-4)+1}\\\\f(-4) = \frac{-12-2}{-4+1}\\\\f(-4) = \frac{-14}{-3}\\\\f(-4) = \frac{14}{3}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%5C%5C%5C%5Cf%28-4%29%20%3D%20%5Cfrac%7B3%28-4%29-2%7D%7B%28-4%29%2B1%7D%5C%5C%5C%5Cf%28-4%29%20%3D%20%5Cfrac%7B-12-2%7D%7B-4%2B1%7D%5C%5C%5C%5Cf%28-4%29%20%3D%20%5Cfrac%7B-14%7D%7B-3%7D%5C%5C%5C%5Cf%28-4%29%20%3D%20%5Cfrac%7B14%7D%7B3%7D)
For g°f[-2]
g°f[-2] is expressed as g(f(-2))
![g(\frac{3x-2}{x+1}) = (\frac{3x-2}{x+1}) + 5\\\\g(\frac{3x-2}{x+1}) = \frac{3x-2}{x+1} + \frac{5(x+1)}{x+1}\\\\g(\frac{3x-2}{x+1}) = \frac{3x-2+5(x+1)}{x+1}\\\\g(\frac{3x-2}{x+1}) = \frac{8x+3}{x+1}\\\\We\ substitute \ in \ [-2] \\\\g(\frac{3x-2}{x+1}) = \frac{8(-2)+3}{(-2)+1}\\\\g(\frac{3x-2}{x+1}) = \frac{-16+3}{-2+1}\\\\g(\frac{3x-2}{x+1}) = \frac{-13}{-1}\\\\g(\frac{3x-2}{x+1}) = 13](https://tex.z-dn.net/?f=g%28%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%29%20%3D%20%20%28%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%29%20%2B%205%5C%5C%5C%5Cg%28%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%29%20%3D%20%20%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%20%2B%20%5Cfrac%7B5%28x%2B1%29%7D%7Bx%2B1%7D%5C%5C%5C%5Cg%28%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%29%20%3D%20%20%5Cfrac%7B3x-2%2B5%28x%2B1%29%7D%7Bx%2B1%7D%5C%5C%5C%5Cg%28%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%29%20%3D%20%20%5Cfrac%7B8x%2B3%7D%7Bx%2B1%7D%5C%5C%5C%5CWe%5C%20substitute%20%5C%20in%20%5C%20%5B-2%5D%20%5C%5C%5C%5Cg%28%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%29%20%3D%20%20%5Cfrac%7B8%28-2%29%2B3%7D%7B%28-2%29%2B1%7D%5C%5C%5C%5Cg%28%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%29%20%3D%20%20%5Cfrac%7B-16%2B3%7D%7B-2%2B1%7D%5C%5C%5C%5Cg%28%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%29%20%3D%20%20%5Cfrac%7B-13%7D%7B-1%7D%5C%5C%5C%5Cg%28%5Cfrac%7B3x-2%7D%7Bx%2B1%7D%29%20%3D%20%2013)
Therefore, the value of f[ -4 ] and g°f[-2] are
and 13 respectively.
Learn more about composite functions here: brainly.com/question/20379727
#SPJ1
Answer:
36 inches
Step-by-step explanation:
Just multipy 3 by 12.